Facebook in tertiary education: The impact of social media in e-Learning - Giannikas, Christina N. (My University, 2020)
The present study provides insights on the impact of using Facebook in e-learning higher education postgraduate programs. More specifically, the study (1) presents the status quo of Facebook in higher education, (2) explores the nature of Facebook in e-learning, and (3) investigates the effects of Facebook on learning community, focusing on their viewpoints. The findings reveal that the majority of the students think favorably of Facebook groups as they conveniently supplement Learning Management Systems (LMS). The survey also indicates that there was an interactive learning element to the use of Facebook that made it more appealing than their university’s Course Management System (CMS) to use during the course.
Keywords: Digital pedagogy; E-learning; Facebook; Student engagement; Tertiary education